2006
DOI: 10.1007/s00401-006-0128-y
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Akt independent of PTEN and CTMP tumor-suppressor gene mutations in epilepsy-associated Taylor-type focal cortical dysplasias

Abstract: Focal cortical dysplasias (FCD) with Taylor-type balloon cells (FCD(IIb)) are frequently observed in biopsy specimens of patients with pharmacoresistant focal epilepsies. The molecular pathogenesis of FCD(IIb), which lack familial inheritance, is only poorly understood. Due to their highly differentiated, malformative nature and glioneuronal phenotype, FCD(IIb) share neuropathological characteristics with lesions observed in familial disorders such as cortical tubers present in patients with autosomal dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 48 publications
4
37
4
Order By: Relevance
“…Interestingly, mutations in PTEN, which negatively regulates both mTOR and -catenin signaling [15], have been demonstrated in HMEG associated with Proteus syndrome [19]. Non-synonymous polymorphisms have been reported in PTEN and TSC1 in CDBC [2,17]; however, no functional PTEN or TSC gene polymorphisms or mutations were detected in our sample of sporadic HMEG cases. These data suggest that sporadic HMEG is genetically distinct from HMEG associated with a and b, 500 microns).…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…Interestingly, mutations in PTEN, which negatively regulates both mTOR and -catenin signaling [15], have been demonstrated in HMEG associated with Proteus syndrome [19]. Non-synonymous polymorphisms have been reported in PTEN and TSC1 in CDBC [2,17]; however, no functional PTEN or TSC gene polymorphisms or mutations were detected in our sample of sporadic HMEG cases. These data suggest that sporadic HMEG is genetically distinct from HMEG associated with a and b, 500 microns).…”
Section: Discussioncontrasting
confidence: 43%
“…The association between phosphorylation of ribosomal S6 protein and enhanced protein synthesis, increased cell size, and expansive tissue growth has been clearly demonstrated in TSC [1,17]. Interestingly, mutations in PTEN, which negatively regulates both mTOR and -catenin signaling [15], have been demonstrated in HMEG associated with Proteus syndrome [19].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changes in TCL1A protein levels in type II FCD lesions, along with cellular distribution, and abnormal expression mechanisms are worth further study. Finally, consistent with the experimental results of Schick et al (2006), we found no change in PTEN expression, indicating that the abnormal activation of AKT in type II FCD lesions might not be associated with PTEN regulatory mutations.…”
Section: Discussionsupporting
confidence: 80%
“…Recent studies in FCD have confirmed activation of pathways, including phosphatidylinositol 3-kinase PIK3 and mTor (9,10,27,28), which have regulatory effects on cell growth and protein synthesis and are implicated in the observed cytomegaly in both neurons and BCs in these lesions. In addition, altered expression of molecules in BCs and DNs, as pAKT (28), in addition to A-catenin (11) in the wnt signaling pathway, have been previously reported in FCD series and may have influence on cell cycle regulation as they are also involved in the regulation and/or degradation of cyclins D and E (21). Based on these observations, the possibility of late G 1 arrest occurring in BCs also merited further exploration.…”
Section: Discussionmentioning
confidence: 99%